Effect of Propolis mouthwash on plaque and gingival indices over fixed orthodontic patients - Dehghani, Mahboobe (J Clin Exp Dent, 2019)
BACKGROUND: In patients with fixed orthodontics, the presence of orthodontic appliances causes dental plaque accumulation and hygiene problems. The purpose of this study was to evaluate the effect of Propolis and chlorhexidine mouthwashes on plaque and gingival indices in patients who are undergoing orthodontic treatment. MATERIAL AND METHODS: In this triple blind study, in total, 37 patients aged from 15 to 35 years those who have been undergoing fixed orthodontic treatment were studied. After that, one of the mouthwashes that containing either Propolis or Chlorhexidine was randomly prescribed to patients. The patients were asked to use mouthwashes twice a day after brushing their teeth for three weeks consecutively. Indicators of plaque, gingival and periodontal status (PI, GI, CPI) were determined on Ramford teeth at the beginning and at the end of three weeks for each patient. Then the results were analyzed statistically. RESULTS: The difference between the values of plaque index (P<0.001), gingival index (P=0.006) and periodontal index (P= 0.005) before and after administration of Propolis were statistically significant. The difference was also statistically significant for all three indexes of plaque (P<0.001), gingival (P=0.001) and periodontal (P=0.003) before and after chlorhexidine mouthwash usage. The indices after using mouthwashes were not statistically significant different between two mouthwash groups. CONCLUSIONS: It seems that Propolis mouthwash can be used as a suitable alternative in patients with fixed orthodontic treatment without the side effects of chlorhexidine mouthwash. Key words:Mouthwash, antimicrobial, Oral hygiene, Propolis, Dental plaque.